Evaluating the impact of improved technology adoption in traditional poultry farming on potential outcomes of farmers: Evidence from rural Togo - Mawussi Kossivi Soviadan; Osama Ahmed; Zaneta Kubik; Anselm Anibueze Enete; Chukwuemeka Uzoma Okoye; Thomas Glauben (Cogent Food & Agriculture, 2024)
Social programs are designed to reach beneficiaries and achieve expected objectives. There is a need to understand whether development programs work and their level of impact on the beneficiaries involved. Along these lines, the objective of this study is to evaluate the impact of Improved Technology adoption in Traditional Poultry Farming (ITTPF) on farmers' potential outcomes in Togo. Baseline and follow-up data were collected from 400 farmers and analyzed using difference-in-differences models. The study reveals that five years after the implementation of the program, the annual gross profit increased on average by US 1294 for each program participant. The results of the heterogeneous impacts assessment indicate that participating in the program is a necessary condition for ITTPF adoption, but not sufficient for profit optimization. Overall, the program has a positive and significant impact on the potential outcomes of farmers in Togo. The government in its agricultural policy should mobilize more resources to enable considerably more farmers to adopt improved agricultural technologies. In addition, agricultural policymakers should implement the instruments of the chain planning, programming, budgeting, execution, monitoring and evaluation of all agricultural development programs and projects to make progressive adjustments for optimal results achievement and sustainable agricultural development.
Keywords: 630; traditional poultry farming; improved technology adoption; impact evaluation; difference-in-differences models; potential outcomes; farmers